Exploring the Privacy and Security Implications in the Adoption of Teleradiology - Damasco Jr, Loreto Bandola; Jallorina, May Jamon; Melon, Gecynth Namo; Ebardo, Ryan Alonsagay (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – This study examines the impact of privacy, security, and individual intentions on teleradiology adoption, with an emphasis on attitudes, social norms, and perceived control. Method – A quantitative approach was employed to assess behavioral intentions toward teleradiology through a survey conducted with 351 experienced respondents from January to March 2024. Using SMART PLS, the survey’s validity was confirmed, with critical metrics meeting reliability thresholds (AVE of 0.5, Cronbach’s alpha, and composite reliability at 0.7). Results – The study’s findings show that perceived security and privacy strongly influence patient trust in teleradiology, while attitudes shaped by benefits and reliability drive adoption. Additionally, social influences and perceived behavioral control motivate the use of teleradiology. Conclusions – Perceived security and privacy significantly affect patients’ attitudes towards adopting teleradiology. Perceived security, in particular, enhances patients' trust and confidence in adopting the technology. A positive attitude, influenced by perceived benefits, usefulness, and reliability, increases the likelihood of adopting teleradiology. Social influence, together with self-efficacy, also impacts patients’ willingness to adopt teleradiology. Recommendations – Future studies should aim for a more balanced representation across all age groups. A more thorough examination of technologies related to data transmission, storage, and access is also recommended. Lastly, a mixed-methods study is recommended for future research. Research Implications – The results highlighted the importance of patient trust and confidence. The study emphasized the need for a patient-centered approach to teleradiology, prioritizing security and privacy to improve the quality of healthcare delivery.